Calculation of mean kidney dose for a Co-57 external radiation source - Supian Samat (Universiti Kebangsaan Malaysia, 1996)
A description is given of the numerical integration method for the calculation of the mean kidney dose for a Co-57 external radiation source. Based on this theory, a computer program was written. Initial calculation of the kidney volume shows that the method has a good accuracy. For the mean kidney dose, this method gives a satisfactory result, since the calculated value lies within the acceptable range of the central axis depth dose.